Effect of external electric field on hydrogen-related defect in amorphous silica. (December 2020) - Wang, Rui; Li, Guo; Yang, Ning; He, An-Min; Duan, Su-Qing; Chu, Wei-Dong
Abstract: The effect of external electric field on the interaction between interstitial hydrogen atoms and defect-free amorphous silica (a-SiO2 ) is studied by means of the reactive force field (ReaxFF) molecular dynamics (MD) simulation and density functional theory (DFT) simulation. We investigate the effects of the hydrogen-atom-hopping and the evolution of interstitial hydrogen atom in a-SiO2 on two kinds of hydrogen-related defect, hydroxyl E' center and [SiO4 /H] 0 center. We find that electric field enhances hydrogen-atom-hopping and the generation of hydroxyl E' center, while does not have significant influence on the formation of [SiO4 /H] 0 center. Moreover, hydroxyl E' center is more stable under electric field. We note that more unstrained Si-O bonds (shorter than 1.7 Å) become active in the reaction of the interstitial hydrogen atom with a-SiO2 under electric field. These effects of electric field on a-SiO2 lead to an increasing of the hydroxyl E' centers, which gives rise to the degradation in performance of microelectronic devices. These results provide a better understanding of the behaviors of hydrogen atoms and the generation mechanism of hydrogen-related defects in a-SiO2, especially under external high electric field.